Murals as an element of urban art and a factor in the development of urban tourism (a case study of Ivano-Frankivsk) - Kovalska, L. V.; Parkhomenko, O. H.; Lutsiv, M. M. (Man and Environment. Issues of Neoecology, 2026)
Purpose. To provide a comprehensive analysis of murals in the city of Ivano-Frankivsk as components of the urban cultural space and objects of tourist attractiveness.Methods. Analysis and synthesis, systematization and classification, cartographic analysis, descriptive method.Results. The conclusions highlight that murals in Ivano-Frankivsk constitute a significant element of the urban cultural landscape and a promising resource for the development of cultural and educational tourism. The study include an analysis of the geospatial distribution and thematic content of murals in Ivano-Frankivsk, as well as the development of an urban art tourist route. It has been established that a distinctive feature of murals as a tourism product is their dynamic nature, characterized by continuous renewal through the emergence of new artworks. The study emphasizes that an important aspect of promoting the tourism product “Murals of Prykarpattia” is raising awareness among local residents about this art form and its culture, alongside the dissemination of an ethical code among amateur artists (muralists). A key constraint identified in the promotion of this art-cultural product within the tourism market is the lack of professionally trained guides specializing in muralism.Conclusions. Their geospatial configuration creates favorable conditions for their integration into the city’s tourism infrastructure as attractive cultural sites. The combination of murals with other cultural and historical locations enables the creation of innovative tour programs, contributing to the diversification of the tourism product.